Vers une sociologie historique de la justice québécoise. Réflexion en marge d'un ouvrage récent sur la justice civile sous le régime français - Belley, Jean-Guy (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
Over the last decade a new trend has emerged in Quebec legal history of which professor J.A. Dickinson's recent book on civil justice under the French Regime is most typical. With quantitative analysis of judicial records as methodology, this research orientation intends to offer a genuine contribution to social history. While recognizing its merits on that account, this paper warns against minimizing the distorsion inherent to the reflection of social life found injudicial records. It is suggested that historical studies ofthat kind should be more properly considered — and with great theoretical benefits — as pertaining to an historical sociology of justice.